Математическая модель процесса электровзрыва цилиндрических проводников - Бакларь, Виктор Юрьевич; Кускова, Наталья Ивановна; Челпанов, Дмитрий Ильич (НТУ "ХПИ", 2015)
Разработана математическая модель электровзрыва цилиндрических проводников, основанная на представлениях о волне испарения. Получены аналитические выражения для временных зависимостей сопротивления, тока, напряжения и давления от параметров электроустановки и характерных размеров проводника в процессе однородного нагрева цилиндрических проводников импульсным током. Экспериментально получены временные зависимости сопротивления, тока и напряжения. Проведено сравнение результатов теоретических и экспериментальных исследований.

The mathematical model of electrical explosion of cylindrical conductors which is based on representations of evaporation wave was developed. Analytical expressions for temporal dependences of resistance, current, voltage and pressure on the parameters of electrical equipment and characteristic sizes of conductor in the process of the homogeneous heating by the impulse current of cylindrical conductors were obtained. Temporal dependences of resistance, current and voltage were experimentally obtained. Qualitative comparison of the developed mathematical model with the results of experimental researches was conducted. Analytical expressions, establishing a connection between impulse pressure in an exploding conductor and electrical power parameters, properties of material and sizes of conductor and external terms, were obtained.
Mathematical model of the process of electrical explosion of cylindrical conductors
Keywords: согласованный режим электровзрыва; волна испарения; ЭВП; evaporation wave; electrical explosion of conductors